2020
DOI: 10.3389/fbioe.2020.566984
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Circular RNA as a Novel Regulator and Biomarker in Preterm Birth

Abstract: Preterm birth (PTB), as the leading cause of neonatal death, is a severe threat to maternal–fetal health. The diagnosis and treatment of PTB are difficult as its underlying mechanism still unknown. Circular RNA (circRNA) is an emerging molecule that plays an essential role in the pathological processes of various diseases. However, it is still unclear whether circRNAs are abnormal or involves in the PTB pathology. In this study, we analyzed RNA-seq data of peripheral blood from preterm and term pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…In samples from maternal circulation (plasma and monocytes), we found that the PTB-related DECs might contribute to the pathological process of PTB by involving the immune-inflammatory response, which is in agreement with our previous finding in peripheral whole blood ( 5 ). In maternal plasma, 33 DECs were identical to those previously identified in peripheral whole blood, and 18 of them showed the same change pattern in both previous and current studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In samples from maternal circulation (plasma and monocytes), we found that the PTB-related DECs might contribute to the pathological process of PTB by involving the immune-inflammatory response, which is in agreement with our previous finding in peripheral whole blood ( 5 ). In maternal plasma, 33 DECs were identical to those previously identified in peripheral whole blood, and 18 of them showed the same change pattern in both previous and current studies.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, the overall molecular changes and underlying mechanisms of PTB have not been well elucidated, which poses challenges for the prediction and treatment of PTB. Recently, the research progress of non-coding RNA (ncRNA) molecules (e.g., circRNA) has provided new ideas for the study of the mechanisms of PTB ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, ncRNAs have proven to be promising biomarkers or targets for treatment of various diseases, including pregnancy complications [ 9 ]. There are few studies on preterm birth and long non-coding RNAs (lncRNAs) [ 10 , 11 , 12 , 13 ] or circular RNAs (circRNAs) [ 14 , 15 ], but the most studied ncRNAs in preterm birth are microribonucleic acids (miRNAs). There are a large number of independent studies searching for the association between miRNAs and common gestational disorders [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 153 miRNAs in maternal peripheral blood were found to be dynamically associated with the gestational week of PTB pregnancies, and bioinformatic analysis further suggested that they were enriched in pathways regulating the immune process [32]. Recently, transcriptomic analysis has shown that circRNAs act as novel biomarkers of PTB and regulate the immune-inflammatory imbalance in PTB [33]. Thus, high-throughput data-based bioinformatics strategies are efficient and comprehensive research methods that have effectuated new perspectives and remarkable breakthroughs in resolving disease perplexities [34][35][36].…”
Section: Introductionmentioning
confidence: 99%